Silicon nanophotonics for mid-IR applications - Mekawey, Hosam Eldin Ibrahim (AUC Knowledge Fountain, 2019)
The research targets the challenge of being able to bring the recently discovered nanophotonics phenomena in the visible spectrum to the Mid-Infrared spectrum in order to be exploited in many mid-IR related applications which include sensing and energy harvesting. In addition to this, the material of choice needs to be silicon in order to take advantage of the low cost, mass fabrication capabilities offered by silicon-based, Complementary Metal Oxide Semiconductor (CMOS) standard fabrication techniques employed in the modern electronics industry. Mainly there are five research points that are being tackled. The first research point has 3 objectives. First, is to investigate and model the effect of plasma dispersion on silicon optical response in order to modulate the phase velocity as well as the absorption coefficient of the material. Second, is to identify the possibility of using silicon with high concentration of excess carriers, introduced either through doping or by optical excitation, instead of metals which are essential in realizing plasmonic-based phenomena in nanophotonics. The third and last objective of the first research point is to investigate the possibility for silicon to generate plasmonic effects in the mid-IR instead of the visible spectrum as the case with metals. Hence bringing many useful nanophotonics attributes to the mid-IR spectrum and the applications related to such spectral range. The second point is to perform modal analysis to identify the fundamental modes in both the rectangular cavity waveguide and the silicon-based slot waveguide due to the critical role they play in many nanophotonics devices and phenomena needed in subsequent research points. Also to investigate ways of engineering the dispersion of such modes in both waveguides. The third point is to investigate the existence of the Extraordinary Transmission (EOT) phenomenon in silicon perforated films. EOT was discovered in perforated metals in 1999. Investigation of the potential of using EOT for mid-IR sensing applications is also an objective. The fourth research point tackles the design of Nano-antenna for sensing applications by realizing an enhancement in the localized electric field in such nanoantenna. Enhanced scattering from silicon nanoparticles with high excess carriers’ concentration and the dynamic real-time tuning of the resonance frequency for sensing and mid-IR spectroscopy applications is part of the objective of the fourth research point. Investigating dipole and bowtie shapes in silicon based nanoantenna and compare their performance with their metallic counterpart is also part of the objective of the fourth research point. Finally a fabrication objective of generating doped and intrinsic silicon nanowires by a single fabrication step through the use of excimer laser and deposited amorphous Silicon film was pursued under this research point. It is expected that the un-doped silicon nanowires can have an enhanced absorption in the visible range in comparison to the flat thin film counterpart. By being able to fabricate doped silicon nanowires, enhancing the absorption in the mid-IR spectrum could be a possibility that can be investigated. Designing a low loss subwavelength optical interconnect on the sub-micrometer level using silicon with high concentration of excess carriers is the fifth research point along with investigating the possibility of enhancing the transmission over bends in real-time through dynamic excess carrier generation. The working wavelength for the optical interconnect is expected to be in the near and mid-IR range. This research exploits recently discovered phenomena in the nanophotonics field and attempts to bring such phenomena to the mid-IR range to be used in the design of novel devices that can provide novel solution for sensing and energy harvesting in such spectrum. Specifically, Extraordinary Transmission (EOT), Localized Surface Plasmon Resonance (LSPR), Surface Plasmon Polariton (SPP), and the light guidance through subwavelength low index material regions are the key phenomena targeted by this research. This research also performs detailed investigation of the properties of subwavelength rectangular and slot waveguides to uncover more of their benefits and characterize their guidance attributes in details. Using Silicon as a material of choice is a priority due to its mature fabrication processes and the possibility of integrating silicon photonics devices into electronics chips using a CMOS-compatible fabrication process. It is also possible to tune the optical response of silicon through doping and excess carrier generation. The possibility for silicon to mimic the behavior of metal at the nanoscale in producing LSPR and SPP-based phenomena by introducing high concentration of excess carriers into silicon is a significant objective of this research which can bring low cost, mass fabrication to plasmonic-based optical devices operating in the mid-IR spectrum.